Effects of Casein Phosphopeptide Amorphous Calcium Phosphate and Casein Phosphopeptide Amorphous Calcium Phosphate Fluoride on Alterations of Dental Plaque PH Following Sucrose Consumption - Haleh Heshmat; Sepideh Banava; Hadi Abdian; Mohammad Javad Kharrazi Fard (Islamic Dental Association of Iran, 2014)
Background and Aim: Plaque pH drop after consumption of sugary materials may dis-solve enamel minerals. Casein phosphopeptide amorphous calcium phosphate (CPP-ACP) is a paste enriched with calcium and phosphate. The new formulation of this paste, casein phosphopeptide amorphous calcium phosphate fluoride (CPP-ACPF), contains 900 ppm fluoride. This paste can neutralize the low pH of bacterial plaque. This study compares the efficacy of CPP-ACP and CPP-ACPF for neutralizing plaque acidity at different time points. Materials and Methods: This clinical trial was conducted on 40 students. Plaque pH at the distal of first molar was measured before and 10 minutes after the consumption of 10% sucrose solution. In the next step, CPP-ACP and CPP-ACPF pastes were applied as recommended by the manufacturers to the tooth surface. Plaque pH was measured at 30 minutes, 60 minutes and 24, 48, 72 and 96 hours. Data was recorded and analyzed by repeated measures ANOVA (p<0.05). Results: Both CPP-ACP and CPP-ACPF increased plaque pH similarly in the first 48 hours. However, the pattern changed from this time point on. Conclusion: CPP-ACP and CPP-ACPF had similar efficacy for up to 48 hours, but CPP- ACPF was capable of keeping the pH high by up to 96 hours.